CULTURE SHOCK DAN HAMBATAN KOMUNIKASI PADA MAHASISWA PERANTAU DI UNIVERSITAS GARUT - Sri Wahyuni, Ayu; Dewi Ningindah , Salma Rosvita (Journal Social Politica, 2023)
Culture shock or better known as culture shock appears as an aspect of acceptance of a new culture where there are different feelings such as fear, confusion, anxiety, worry for new individuals, and entering a new cultural phase or new scope. Many challenges must be experienced when students become immigrants in different areas with different cultures, besides that as immigrant students must be able to adapt to the surrounding culture slowly so that later it can become a new habit and get used to that culture, not many students Many immigrants can accept a new culture quickly, many of whom are undergoing the process. With the diversity that is owned on the Garut University campus where students do not only come from the Garut area, one of the aims of this paper is to find out and describe what are the obstacles for students outside of Garut experiencing Culture Shock at Garut University in terms of what aspects. The majority of students are from the Garut or Sunda areas. The intended target and used are students from overseas outside the Garut area, especially at the Faculty of Communication and Information Sciences. The theoretical concept in this paper uses the theory of intercultural communication and uses the active interview method on the informants then reviewed again with interactive analysis techniques, it will usually be known what forms of obstacles are the obstacles in oneself to fulfill and ensure the data exists. by interviewing a student from Papua whose culture and daily life are quite different.